The Influence of Animated Video on Knowledge and Compliance of Pregnant Women About Tetanus Toxoid Immunization - Ruliyanti Ruliyanti; Andi Wardihan Sinrang; Mardiana Ahmad; Ariyanti Saleh; Sharvianty Arifuddin; Stang Stang (Poltekkes Kemenkes Palu, 2023)
Pregnant mothers who are unaware of the risks of tetanus during pregnancy are more likely to die giving delivery or have their children die at birth. This study aimed to analyze the effect of sinusoidal runaway animation on the knowledge and adherence of pregnant women regarding tetanus toxoid immunization at the Tabongo Health Center. This study uses the Research and Development method with the Borg and Galt development model which will be used to develop and validate an animated video product. In combination with the quasi-experimental design, quantitative method using a nonequivalent control group design approach to determine the condition of the subjects in the intervention group and the control group before and after treatment. The study population comprised 265 pregnant women in the Tabongo Health Center area. A sample of 74 pregnant women was divided into two groups: intervention and control. The mothers’ knowledge before being given Rumawa Sinusoid Animation education in the majority intervention group averaged 59.14. Mothers' knowledge after receiving Rumawa Sinusoid Animation education in the majority intervention group averaged 79.43. Mothers’ knowledge before being given Text Animation education in the majority of the control group averaged 63.95. Mothers' knowledge after being given Text Animation education in the majority of the control group averaged 82.24. In Conclusion, Rumawa Sinusoid Animation Education's influence on increasing pregnant women's knowledge and compliance regarding Tetanus Toxoid immunization. It is hoped that further research using sound and images will also be investigated to provide varied results.